Response of some mango-infesting fruit flies to aqueous solutions of the basil plant Ocimum tenuiflorum L - Niassy, Saliou; Mohamed, Samira Abuelgasim; Cheseto, Xavier; Omuse, Evanson Rigan; Ochola, John Bwire; Khamis, Fathiya Mbarak; Badji, Boubacar; Ndlela, Sheppard; Ombura, Levi; Okun, Noelah Leah; Kupesa, David Mfuti; Dubois, Thomas; et al. (Frontiers in Horticulture, 2023)
Abstract This study evaluated the potential of holy basil (Ocimum tenuiflorum L.) as an alternative attractant for tephritid fruit flies, which threaten horticultural sectors in Africa. In laboratory experiments, we used a dual choice olfactometer to assess the attraction of adult oriental fruit fly Bactrocera dorsalis (Hendel) to intact plants, 100 µL commercial methyl eugenol (ME) (positive control), 10 mg/mL of O. tenuiflorum aqueous extract (Otae), and a negative control (blank). Large arena experiments were conducted to compare responses of four fruit fly species of economic importance in Africa to Otae-baited traps. In dual choice olfactometer assay, more B. dorsalis males (78.6%) than females (23.8%) were attracted to Otae. Most B. dorsalis males were attracted to the positive control (90.5%) and 10 mg/mL Otae (88.5%) compared to the whole plant (84.0%). In large arena experiments, Otae attracted the most B. dorsalis males (47.7%) followed by Zeugodacus cucurbitae males (25.1%) while males of Ceratitis species were the least attracted. The analysis of headspace volatiles from aerial plants, Otae and essential oil using gas chromatography-mass spectrometry detected 97 compounds. The intact plant without flowers, intact plant with flowers, Otae, and the O. tenuiflorum essential oil contributed 76, 62, 33 and 28 compounds, respectively. ME comprised top three most abundant compounds, especially in the essential oil. Our study confirms the potential of O. tenuiflorum as a source of ME for tephritid fruit fly integrated management in Africa. Otae, a readily available alternative to commercial ME, can be used to develop fruit fly baited traps, particularly for smallholder farmers. Keywords: Bactrocera dorsalis, methyl eugenol, fruit fly, Ocimum tenuiflorum, behavioral response